Canadian cinema since the 1980s : at the heart of the world - Pike, David L. (David Lawrence), 1963- (University of Toronto Press, 2012)
Making a significant advance in the study of the film industry of the period, Canadian Cinema since the 1980s is also an ideal text for students, researchers, and Canadian film enthusiasts.